The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2000
DOI: 10.1677/joe.0.1650253
|View full text |Cite
|
Sign up to set email alerts
|

Binding characteristics of pro-insulin-like growth factor-II from cancer patients: binary and ternary complex formation with IGF binding proteins-1 to -6

Abstract: Many tumours secrete IGF-II in incompletely processed precursor forms. The ability of these pro-IGF-II forms to complex with the six IGF binding proteins (IGFBPs) is poorly understood. In this study, pro-IGF-II has been extracted from the serum and tumour tissue of two patients with non-islet cell tumour hypoglycaemia. These samples were used to study binary complex formation with IGFBPs-1 to -6 using competitive IGF-II binding assays and ternary complex formation with IGFBP-3 and IGFBP-5.In each case, IGFBPs-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
50
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(55 citation statements)
references
References 36 publications
5
50
0
Order By: Relevance
“…The findings presented here have also confirmed that IGFBP-2, IGFBP-3, and IGFBP-5 bind all IGF-II isoforms similarly to mature IGF-II, in agreement with Bond et al (16) but not with Elmlinger et al (17), who reported that pooled isolates of IGF-II isoforms from Ewing's sarcoma cell conditioned media appeared to retard binary complex formation with IGFBP-2 and IGFBP-3. Our approach has also confirmed early findings that IGFBP-3-based ternary complex formation by glycosylated IGF-II isoforms is severely compromised (16) and has refined these findings to show that big-IGF-II 1-87 and big-IGF-II 1-104 are the most potent at preventing its assembly.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The findings presented here have also confirmed that IGFBP-2, IGFBP-3, and IGFBP-5 bind all IGF-II isoforms similarly to mature IGF-II, in agreement with Bond et al (16) but not with Elmlinger et al (17), who reported that pooled isolates of IGF-II isoforms from Ewing's sarcoma cell conditioned media appeared to retard binary complex formation with IGFBP-2 and IGFBP-3. Our approach has also confirmed early findings that IGFBP-3-based ternary complex formation by glycosylated IGF-II isoforms is severely compromised (16) and has refined these findings to show that big-IGF-II 1-87 and big-IGF-II 1-104 are the most potent at preventing its assembly.…”
Section: Discussionsupporting
confidence: 92%
“…Unglycosylated pro-IGF-II (1-156) and big-IGF-II (1-104), both produced in E. coli, were purchased from GroPep (Australia). Purified human IGFBP-2, IGFBP-3, and IGFBP-5 have been described elsewhere (16). The anti-IR mAb 83-7 and the anti-IGF-IR mAb 24-31 were produced in-house (23,24).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Valenzano et al (1997) found no difference in the binding to IGFBP-1 and IGFBP-3 of the foetal bovine high M r weight forms of IGF-II. Binding characteristics of pro-IGF-II, extracted from tumours or serum from patients with cancer, to IGFBP-1 to -6 were established: precursor forms of IGF-II did not show any difference from mature IGF-II in their binding to IGFBPs (Bond et al 2000), except for the formation of a ternary complex with the acid labile subunit (ALS) and IGFBP-3. However, ALS is absent from AF.…”
Section: Discussionmentioning
confidence: 99%
“…In normal human serum, about 70-80% of the mature IGF-II form a ternary 150 kDa complex with IGF-BP3 and its acid-labile subunit. By contrast, the HMW form of IGF-II, which is not able to form the ternary complex, primarily forms a smaller binary 40 kDa complex with IGFBPs [10]. A binary complex can pass more readily through the capillary membrane due to its small molecular size to exert its insulin-like effects on target tissues via insulin receptors [9].…”
Section: Discussionmentioning
confidence: 99%